Reading ability in both deaf and hearing adults is linked to neural representations of abstract phonology derived from visual speech - Samuel Evans; Cathy J. Price; Jörn Diedrichsen; Tae Twomey; Indie Beedie; Maggie Fraser; Mairéad MacSweeney (Proceedings of the National Academy of Sciences, 2026)
Reading is central to academic and vocational success. Some deaf children face reading challenges due to limited access to spoken or signed language. Robust phonological representations are key to reading development in hearing children. Spoken language phonology may be one of many contributors to reading development in deaf children. Indeed, speechreading ability correlates with reading skill in both deaf and hearing individuals, suggesting it is linked to reading development regardless of hearing status. Further support for this hypothesis would be provided by evidence that similar neural representations of speech phonology are evoked by visual speech and other language forms (auditory speech and text) and that these neural representations are related to reading proficiency. We used fMRI and representational similarity analysis (RSA) to identify shared neural representations of spoken language phonological structure. A group of deaf adult participants (N = 22), with a mixture of sign language and spoken language backgrounds and reading abilities, were presented with single lexical items as visual speech and dynamic text (cursive text, revealed letter-by-letter to promote a phonological reading strategy). Adult hearing participants (N = 25) were presented with the same words, but as visual speech and auditory speech. Shared neural representations of phonological structure of English words were found in each group in the superior and middle temporal cortex (STC/MTC) and these abstract representations were more similar across different language forms in better readers. Our data provide neurobiological evidence of the contribution of visual speech to abstract phonological representations of spoken language, that relate to reading proficiency, in both deaf and hearing adults.